1973
DOI: 10.1038/bjc.1973.182
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Antibody Studies in Malignant Melanoma

Abstract: Summary.-Sera from 57 patients with malignant melanoma and 39 control patients were tested by immunofluorescence techniques against 6 melanoma cell lines. Thirty-two per cent of tests with sera from melanoma patients showed fluorescence with these cell lines whereas only 1700 of tests with control sera were positive. Reactions occurred in 210o of tests with sera from patients with primary melanoma compared with 4000 with secondary melanomata and 5400 with " cured " melanomata. The cell lines varied in antigeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1975
1975
1982
1982

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…It is possible that this antibody represents an auto-response to the antigen demonstrated by Allerton et al (1970) and by Bur in and Gendron (1973) and we propose to investigate this possibility There is no comparable study of antibodies to cytoplasmic antigens in children with Wilms' tumour, but the incidence of antibodies detectable by fluorescent methods against other tumours has tended to be higher. Thus in malignant melanoma the incidence has varied from 21 % (Whitehead, 1973) to 100% (Muna et al, 1969) and in a variety of sarcomas has been reported as approximately 36% (Moore et al, 1973;Drewinko et al, 1973). On the other hand, in a personal unreported series of 70 sera from adults suffering from a variety of adenocarcinomata, none contained antibody demonstrable by fluorescence techniques to react specifically with tumour cells.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that this antibody represents an auto-response to the antigen demonstrated by Allerton et al (1970) and by Bur in and Gendron (1973) and we propose to investigate this possibility There is no comparable study of antibodies to cytoplasmic antigens in children with Wilms' tumour, but the incidence of antibodies detectable by fluorescent methods against other tumours has tended to be higher. Thus in malignant melanoma the incidence has varied from 21 % (Whitehead, 1973) to 100% (Muna et al, 1969) and in a variety of sarcomas has been reported as approximately 36% (Moore et al, 1973;Drewinko et al, 1973). On the other hand, in a personal unreported series of 70 sera from adults suffering from a variety of adenocarcinomata, none contained antibody demonstrable by fluorescence techniques to react specifically with tumour cells.…”
Section: Resultsmentioning
confidence: 99%